2019
DOI: 10.1111/jvh.13243
|View full text |Cite
|
Sign up to set email alerts
|

Point of care and oral fluid hepatitis B testing in remote Indigenous communities of northern Australia

Abstract: Many Indigenous Australians in northern Australia living with chronic hepatitis B are unaware of their diagnosis due to low screening rates. A venous blood point of care test (POCT) or oral fluid laboratory test could improve testing uptake in this region. The purpose of this study was to assess the field performance of venous blood POCT and laboratory performance of an oral fluid hepatitis B surface antigen (HBsAg) test in Indigenous individuals living in remote northern Australian communities. The study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(130 reference statements)
0
5
0
Order By: Relevance
“…The cause of the reported lower sensitivity in HIV-coinfected populations [ 39 , 40 , 43 , 44 ] is unclear, but potential reasons may include the cross reaction of HIV-reverse transcriptase inhibitors and hepatitis B virus, a higher rate of occult hepatitis B infection in early HIV cohorts, a higher reported rate of HBsAg loss in both untreated and treated HIV-infected populations and the use of tenofovir-based HIV regimens that effectively suppress hepatitis B virus DNA levels and a large decline in HBsAg titres [ 31 , 45 , 46 ]. SD Bioline HBsAg [ 38 , 47 , 48 , 49 ] and VIKIA HBsAg POC test [ 32 , 33 , 38 , 50 , 51 ] have also been shown to have good sensitivity (above 90%) and excellent specificity (above 99%) in general populations; however, lower sensitivity was also reported in HIV-infected populations [ 40 ].…”
Section: Poc Tests For Hepatitis B and Their Clinical Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The cause of the reported lower sensitivity in HIV-coinfected populations [ 39 , 40 , 43 , 44 ] is unclear, but potential reasons may include the cross reaction of HIV-reverse transcriptase inhibitors and hepatitis B virus, a higher rate of occult hepatitis B infection in early HIV cohorts, a higher reported rate of HBsAg loss in both untreated and treated HIV-infected populations and the use of tenofovir-based HIV regimens that effectively suppress hepatitis B virus DNA levels and a large decline in HBsAg titres [ 31 , 45 , 46 ]. SD Bioline HBsAg [ 38 , 47 , 48 , 49 ] and VIKIA HBsAg POC test [ 32 , 33 , 38 , 50 , 51 ] have also been shown to have good sensitivity (above 90%) and excellent specificity (above 99%) in general populations; however, lower sensitivity was also reported in HIV-infected populations [ 40 ].…”
Section: Poc Tests For Hepatitis B and Their Clinical Performancementioning
confidence: 99%
“…Innovations in sampling technique have provided more convenient specimen collection methods, such as using oral fluid as specimen collected by an oral swab [ 25 , 48 , 51 ]. The simplified process was highly acceptable to individuals [ 25 , 48 ], but testing accuracy is a challenge to overcome [ 48 ], and it may additionally require trained technicians or lab-based enzyme immunoassays or equipment for sample preparation such as requiring a centrifuge for target analyte separation [ 51 ]. Future development needs to consider combining sample preparation steps together with detection and readout into one single device, without sacrificing testing accuracy.…”
Section: Poc Tests For Hepatitis B and Their Clinical Performancementioning
confidence: 99%
“…Indeed, a metaanalysis that included 30 studies evaluating the performance of 33 different HBsAg LFTs found an overall sensitivity of 90.0% (95% CI, 89.1-90.8%) and specificity of 99.5% (95% CI, 99.4-99.5%) [88]. More recent evaluations of commercial HBsAg LFTs have shown sensitivities above 91% and specificities above 94% [89][90][91]. Mutations within the antigenic determinants of HBsAg appear to have little impact on the performance of certain HBsAg LFTs, although this may depend on the specific antigen epitopes that are recognized by the antibodies used in the test [92].…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…Where this is not feasible, evidence‐based models of outreach specialist care should be implemented in collaboration with Indigenous communities. Indigenous nurse practitioners embedded within multidisciplinary liver disease teams, integration of hospital and remote health services through telehealth initiatives (eg, the Project ECHO model of care [https://hsc.unm.edu/echo/], where primary care workers can discuss cases with specialists via virtual case conferences in regional and remote areas), and Indigenous peer‐led navigation of health service programs have successfully improved liver disease screening, management and cancer surveillance uptake here and overseas 18‐23 …”
mentioning
confidence: 99%
“…Medicare rebate reforms to sustain telehealth initiatives developed during the coronavirus disease 2019 pandemic would be beneficial. Incorporating viral hepatitis diagnostic point‐of‐care tests into nurse‐led models of care could overcome barriers to diagnostics access in remote communities 18 . Public–private initiatives to financially support Indigenous health worker training are imperative to increase and retain the Indigenous health workforce.…”
mentioning
confidence: 99%